1993
DOI: 10.1007/bf01953986
|View full text |Cite
|
Sign up to set email alerts
|

Growth and growth hormone in children during and after therapy for acute lymphoblastic leukaemia

Abstract: Growth impairment and growth hormone (GH) deficiency have been reported in children treated for acute lymphoblastic leukaemia (ALL). We have studied growth and GH secretion in a group of 50 patients, affected by ALL, during a 2- to 5-year period after diagnosis, and in 12 "long-term-survivors". We observed a significant decrease in growth velocity during the 1st year (in particular during the first 6 months) of therapy and a catch-up growth after the end of therapy. "Long-term survivors" did not exhibit a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
15
2
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 21 publications
(33 reference statements)
9
15
2
1
Order By: Relevance
“…Femur length does not contribute to the mouse length as conventionally measured. This could explain the lack of difference in length, weight, and BMI among all groups in our study, contrary to what was found by follow-up studies of adult childhood cancer survivors [Crofton et al 2000;Caruso-Nicoletti et al 1993].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Femur length does not contribute to the mouse length as conventionally measured. This could explain the lack of difference in length, weight, and BMI among all groups in our study, contrary to what was found by follow-up studies of adult childhood cancer survivors [Crofton et al 2000;Caruso-Nicoletti et al 1993].…”
Section: Discussioncontrasting
confidence: 99%
“…An argument could be made as to whether the impairment is a direct effect of CTX on bone development, a growth hormone deficiency from pituitary damage, or a combination of the two. However, a growth hormone deficiency would be reflected in a long-term deficiency in height and weight, which was not observed in this study or human studies [Caruso-Nicoletti et al 1993]. Femur length does not contribute to the mouse length as conventionally measured.…”
Section: Discussioncontrasting
confidence: 54%
“…Multiple high dose chemotherapy is now an important part of the standard treatment for childhood malignancies, and while this form of treatment has become more successful, adverse long term side effects on growing skeleton have been noted including growth arrest, osteoporosis and fracture. [2][3][4][5][6][7][8] The sensitivity of the immature skeleton to chemotherapy has also been documented in animal studies. [9][10][11][12][13][14] Future trend for treatment of childhood malignancies looks set to involve further intensified use of chemotherapy, and therefore further understanding and characterization of the mechanisms by which chemotherapy disrupts bone growth is important.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports of poor growth in children with acute lymphoblastic leukemia (ALL), especially during periods of intensive chemotherapy, but growth may return to normal during less-intensive periods and may show evidence of further catch-up after completion of chemotherapy (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Of greater concern are a number of retrospective crosssectional studies on survivors of ALL that describe reduced bone mineral density (BMD) at various sites (14 -16).…”
mentioning
confidence: 99%